Conducting Psychoeducation to Covid-19 Survivors with Anxiety Disorder - Dyta Setiawati Hariyono (UMBanjarmasin, 2021)
Anxiety is defined as a condition of apprehension and worried if something bad will happens. The emergence of feeling anxiety is due to a suitable response toward a threat. However, anxiety has called abnormal when the portion exceeds the threat itself or arises with no reason, which is not a response to environmental change. This research aims to determine the effect of conducting Psychoeducation toward Covid-19 survivors with anxiety disorder so that it can overcome the anxiety of Covid-19 survivors either while being or after being exposed to Covid-19. In addition, the researcher also hopes that this research can enhance public knowledge as a preventive action in facing anxiety disorder during the pandemic. The Psychoeducation method was applied to 16 participants of Covid-19 survivors in Banjarmasin. It was conducted by instructors and resource persons from Lecturers of the Faculty of Psychology, University of Muhammadiyah Banjarmasin. The Psychoeducation was carried out through Zoom Meetings. There were five sections during the activities, namely, session 1 (opening and introduction), session 2 (sharing experiences for Covid-19 survivors, followed by Covid-19 & anxiety materials), session 3 (ice-breaking), session 4 (question and answer), and session 5 (relaxation). Applying Psychoeducation by presenting anxiety disorder material and giving relaxation was proven as a method to overcome the feeling of anxiety and make participants more relaxed during a pandemic.